Micropigmentation - Amit S Kerure; Manjot Marwah; Nitika Deshmukh Wagh; Satish Udare (Wolters Kluwer Medknow Publications, 2023)
Micropigmentation and microblading is a popular technique now a days which is used as a semi permanent method for camoflaging various dermatological indications. This article will elaborate upon various indications of micropigmenation. Micropigmentation is used in variety of dermatological conditions like semi permanent make up and vitiligo (stable forms). In this technique, a thorough knowledge of the indication and colour theory is crucial to achieve near to natural output. Micropigmentation or medical tattooing is a novel and easy to learn technique to camouflage various dermatological conditions like stable vitiligo, alopecia (androgenetic alopecia or stable alopecia areata) as well as for semi permanent make up.